Letter from Svante Arrhenius to Georg Bredig, February 26, 1921 - Arrhenius, Svante (1921)
Letter from Svante Arrhenius (1859-1927) to Georg Bredig (1868-1944). Contains personal updates about Arrhenius' family as well as updates about the Experimentalfältet (The Fields for Experiments at the Royal Swedish Academy of Agriculture and Forestry). Arrhenius often writes to Bredig about world affairs, politics, and the economy.
Keywords: Arrhenius, Svante, 1859-1927; World War (1914-1918); Kungl. Lantbruksakademien (Sweden). Experimentalfältet; Politics and government; Bredig, Georg, 1868-1944